Antinociceptive and antiinflammatory activities of crude leave extract and solvent fractions of Commelina latifolia Hochst. ex C.B.Clarke (Commelinaceae) leaves in murine model - Tadege, Getnet; Sirak, Betelhem; Abebe, Dehnnet; Nureye, Dejen (Frontiers in Pharmacology, 2023)
Ethnopharmacological relevance: In the past, Ethiopian traditional medicine employed the leaves of the native Commelina latifolia Hochst. ex C.B. Clarke plant to treat wounds, pain, and malaria. Aim of the study: The crude extract and solvent fractions of Commelina latifolia Hochst. ex C.B.Clarke leaves were examined in the present investigation to determine their ability to have an antiinflammatory effect and provide an antinociceptive effect in animal models.The leaves of C. latifolia were extracted with 80% methanol, and the CL crude extract was further fractionated with chloroform, pure methanol, and distilled water. The carrageenan-induced paw edema model was used to test the extracts' ability to reduce inflammation. The hotplate model and the acetic acid-induced writhing test on rodents were used to test the extracts' potential antinociceptive effect to reduce pain.2 Results: Inflammation was decreased by 64.59% with CL crude extract (400 mg/kg); 56.34% (400 mg/kg) of methanol fraction, 64.59% of aqueous fraction (400 mg/kg), and 38.27% of chloroform fraction in the carrageenan-induced inflammatory model. All extracts demonstrated a considerable lengthening of the nociception reaction time in the hot plate test, with a maximum antinociceptive effect of 78.98% (crude extract) and 71.65% (solvent fractions). At a dosage of 400 mg/kg, the natural Commelina latifolia crude extract and aqueous fraction demonstrated considerable antinociceptive effects against acetylsalicylic acid (ASA) during the writhing test (48.83% and 45.37than%, respectively). The current findings support Ethiopia's traditional user's assertions that the herb can alleviate inflammation and pain.